Biological activity of oestradiol sulphate in an oviparous amniote: implications for maternal steroid effects - Paitz, Ryan T. (The Royal Society, 2011)
Understanding the many factors that underlie phenotypic variation is of profound importance to evolutionary biologists. The embryonic endocrine environment is one such factor that has received much attention. In placental amniotes, the dynamic interaction of maternal and embryonic steroid production and metabolism is critical to regulating the endocrine environment. Less is known about how embryos of oviparous amniotes regulate their endocrine environment because most studies have focused on relating initial steroid levels in the yolk at oviposition to offspring phenotype. We tested the hypothesis that embryos of oviparous amniotes regulate their endocrine environment by conjugating maternal steroids and subsequently using the metabolites as precursors for steroid production later in development. Using the red-eared slider turtle (Trachemys scripta), we first characterized the conjugation of exogenous oestradiol to either oestradiol glucuronide or oestradiol sulphate (E(2)-S) in ovo during the first 15 days of development. Results show that oestradiol is primarily conjugated to E(2)-S. We then examined whether E(2)-S influenced sex determination and report that E(2)-S increases the production of female offspring. These data demonstrate that oviparous amniotes can both sulphonate steroids and respond to sulphonated steroids during embryonic development in a manner similar to placental amniotes.